2015
DOI: 10.1002/ab.21632
|View full text |Cite
|
Sign up to set email alerts
|

Entitled vengeance: A meta‐analysis relating narcissism to provoked aggression

Abstract: Narcissism has long been used to predict aggressive or vengeful responses to provocations from others. The strength of this relation can, however, vary widely from study to study. Narcissism and revenge were examined in 84 independent samples (N = 11297), along with the moderating role of sample type (i.e., child/adolescent, prisoner, undergraduate, or general samples), type of narcissism measure used (i.e., Narcissistic Personality Inventory, Psychological Entitlement Scale, Short D3, etc.), the nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 134 publications
7
55
0
1
Order By: Relevance
“…Indeed, it has been argued that aggressive behavior serves a regulatory function for individuals high in narcissism (e.g., Ronningstam, 2009). Studies examining provoked aggression in the laboratory have been interpreted as such (Rasmussen, 2016). We similarly found that perceptions of others’ behavior and one’s own quarrelsomeness were linked, and amplified by one’s level of narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been argued that aggressive behavior serves a regulatory function for individuals high in narcissism (e.g., Ronningstam, 2009). Studies examining provoked aggression in the laboratory have been interpreted as such (Rasmussen, 2016). We similarly found that perceptions of others’ behavior and one’s own quarrelsomeness were linked, and amplified by one’s level of narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…A promising direction involves examining narcissism itself as a state, given narcissistic thoughts and emotions also vacillate over time (Giacomin & Jordan, 2016). Recent examinations of such narcissistic states suggest they are sensitive to inter-personal events (e.g., having power) as well as indicative of fluctuations in affect and self-esteem (Giacomin & Jordan, 2014a, 2014b, 2016. Critically, narcissistic states themselves seem to be multifaceted and differentially indicative of narcissistic grandiosity and vulnerability (Giacomin & Jordan, 2016).…”
Section: Moving the Study Of Narcissism Forwardmentioning
confidence: 99%
“…Narcissism has both grandiose manifestations (such as boastful, aggressive behavior) and vulnerable manifestations (such as a fear of being evaluated negatively; Krizan & Herlache, ; Pincus & Lukowitsky, ). Even in its subclinical form, narcissism predicts maladjustment ranging from aggression and violence to addiction and depression (Carter, Johnson, Exline, Post, & Pagano, ; Dawood & Pincus, ; Larson, Vaughn, Salas‐Wright, & Delisi, ; Rasmussen, ). In its extreme form, narcissism can develop into narcissistic personality disorder, marked by “a pervasive pattern of grandiosity (in fantasy or behavior), need for admiration, and lack of empathy” (American Psychiatric Association, ).…”
Section: Introductionmentioning
confidence: 99%